Aunt Bernice - Gantos, Jack.; Rubel, Nicole (Boston : Houghton Mifflin, 1978)
Despite the calamitous experiences of Aunt Bernice and her awful dog, Ida learns to love her outrageous relative.
Keywords: Aunts -- Fiction